OPTIMALISASI MARKETING SKILL SYARIAH MAHASISWA MELALUI BUSINESS WRITING DAN ANALISIS BISNIS - Abdurrahman Abdurrahman; Zuhrinal M. Nawawi (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
In an increasingly competitive and digitally driven business era, students of Islamic economics and banking are required to possess marketing skills that are not only strategic but also ethical and communicative. This article aims to examine how the integration of business writing and business analysis skills can optimize students’ Islamic marketing competencies. Effective business writing enables the delivery of professional, transparent, and value-driven communication, while business analysis provides a strong strategic foundation for understanding the market and formulating marketing decisions. Using a literature study method, this article identifies the importance of synergy between these two skills in creating communication strategies that are both efficient and aligned with Islamic values. The results of the discussion show that mastering business writing and analytical capabilities significantly enhances students’ competencies in developing relevant, trustworthy, and value-oriented Islamic marketing plans.